Water usage optimization of smart farm automated irrigation system using artificial neural network - Dela Cruz, John R. (Animo Repository, 2017)
Limited water resources had become the main constraint to be considered in farming. Optimizing this has become one of the interests in researches relating to precision agriculture. In this paper, the researchers use Neural Network in optimizing the water usage in the smart farm by incorporating it to the proposed Smart Farm Automated Irrigation System (SFAIS) by implementing an expert system. Simulations were done using the MATLAB Neural Network toolbox and results show that neural network is a useful tool. © 2017 IEEE.